Upaya Meningkatkan Kemampuan Kecerdasan Kinestetik Melalui Pembelajaran Seni Tari Kreasi Pada Siswa Kelas III Di SDN 10 Gunung Terang - Dimas Satria; Fauzi Fadliansyah (Desanta Publisher, 2024)
The research aims to: 1). Knowing the objective conditions of children's kinesthetic intelligence before participating in the dance learning process. 2). Knowing the process of implementing dance learning to improve children's kinesthetic intelligence. The population of this research data is students. The results of this research show that: 1). Early kinesthetic intelligence in children by teachers is relatively still using conventional methods in learning. Dance is only limited to sports and games that are related to kinesthetic intelligence. 2). The process of learning creative dance media steps is taken through simple, not complicated implementation stages 3). Learning Results: Creative Dance media in certain forms has contributed to improving children's kinesthetic intelligence in general, especially when they start to move their bodies and coordinate with their hands, feet and head flexibly, which requires practice, concentration and creative thinking. Based on the results of the discussion that has been described, learning activities using creative dance have a big impact on increasing children's kinesthetic intelligence.